Influence of Regional Differences in the Cost of Living on National Income Inequality - Surinov, Alexandr E.; Luppov, Artur B. (Economy of Regions, 2021)
Regional differences in the cost of living distort the estimates of monetary components of living standards and resource requirements, which are necessary for implementing measures to reduce income inequality as a cause of social injustice and unrest. Thus, we propose a methodology for calculating nominal household income using rouble purchasing power parity to assess its influence on national inequality. This approach measures inequality based on individual data on household income, disregarding the territorial differentiation of consumer prices. Then, the influence of regional price differences on the national income inequality was assessed by comparing Gini coefficients calculated for the same sample of households using two criteria: nominal per capita income and per capita income adjusted for purchasing power in various regions. The study revealed that the difference in nominal incomes is reduced by regional disparities in the cost of living. Simultaneously, the distribution of household incomes adjusted for regional purchasing power parities is more even. The research findings can be used to develop policy measures aimed at reducing regional welfare disparities and poverty.